Upaya Meningkatkan Motivasi Belajar Siswa Menggunakan Model Pembelajaran Project Based Learning - Hayatun, Miftahul; Arjudin, Arjudin; Kaninta, Novianti (Journal of Science Instruction and Technology, 2023)
The learning process found students with different learning motivations, so a learning model is needed that can increase student learning motivation, namely the Project Based Learning model. The purpose of this research is to increase students' learning motivation using the Project Based Learning learning model in class IV B of SDN 50 Cakranegara for the 2022/2023 academic year. Research data was collected through a questionnaire that measures 4 elements of motivation, namely attention, relevance, confidence, and satisfaction (ARCS) through a learning model. The results of class action research showed that in the first cycle the percentage of students who were motivated was 80%, and in the second cycle it increased to 87%. Thus it is concluded that the application of the Project Based Learning learning model can increase student motivation.